2018
DOI: 10.1186/s12929-018-0456-y
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 exacerbates survival of cancer stem-like tumorspheres in EGFR-positive colorectal cancers: RNAseq analysis and therapeutic screening

Abstract: BackgroundCancer stem cells are capable of undergoing cell division after surviving cancer therapies, leading to tumor progression and recurrence. Inhibitory agents against cancer stem cells may be therapeutically used for efficiently eradicating tumors. Therefore, the aim of this study was to identify the relevant driver genes that maintain cancer stemness in epidermal growth factor receptor (EGFR)-positive colorectal cancer (CRC) cells and to discover effective therapeutic agents against these genes.MethodsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
(53 reference statements)
2
22
0
Order By: Relevance
“…The overexpression of Lgr5 in the colorectal cancer cells occurs due to up or downregulation of several noncoding RNAs, such as CASC15 miR-4310 or miR-23a, as a consequence of activation of PI3K/Akt signaling pathway (Takahashi et al 2011 ; Mukohyama et al 2017 ). Other studies have also emphasized the role of EGF/EGFR/STAT3/PDGFA pathway and histone acetylation on the Lgr5 promoter (Cheng et al 2017 , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of Lgr5 in the colorectal cancer cells occurs due to up or downregulation of several noncoding RNAs, such as CASC15 miR-4310 or miR-23a, as a consequence of activation of PI3K/Akt signaling pathway (Takahashi et al 2011 ; Mukohyama et al 2017 ). Other studies have also emphasized the role of EGF/EGFR/STAT3/PDGFA pathway and histone acetylation on the Lgr5 promoter (Cheng et al 2017 , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…HCC116-and HT29-derived tumorspheres were cultured in serum-free DMEM medium containing individual 20 ng/mL of epidermal growth factor (EGF), basic fibroblast growth factor (bFGF), hepatocyte growth factor (HGF), and interleukin (IL)-6, which are sensitive to STAT3 inhibitors [ 9 ]. Stemness markers, including CD133 and LGR5, were detected at first; it indicated that HCT116 was a CD133-positive cell line (97.5% CD133 expression); however, only 0.93% of LGR5 expression was observed in these cells ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, STAT3-upstream signals may be activated under regorafenib-induced stressful conditions [ 17 , 18 ], leading to STAT3 activation. Moreover, additive growth factors for tumorsphere formation, such as EGF and IL6, can phosphorylate STAT3 in cancer cells [ 9 , 13 , 19 ]. Thus, tumorspheres with constitutive STAT3 activation are expected to be resistant to regorafenib-inhibited cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, U-87 MG (HTB-14™, ATCC®) cell line was employed, which are cells derived from Homo sapiens malignant gliomas that overexpresses EGFR [14]. On the other hand, HT-29 (HTB-38™, ATCC®), derived cells from Homo sapiens colorectal adenocarcinoma EGFRoverexpressing [15], was also included as manner to potentially expand BNCT-strategy in other tumoral-pathology [8]. The studied hybrids 1-10 were active, displaying different level of cytotoxicities against both mammal-cells ( Table 2).…”
Section: In Vitro Activity Against Other Overexpressing Egfr-cellsmentioning
confidence: 99%